2008
DOI: 10.1007/s12160-008-9045-8
|View full text |Cite
|
Sign up to set email alerts
|

Are Cholesterol and Depression Inversely Related? A Meta-analysis of the Association Between Two Cardiac Risk Factors

Abstract: TC and depression were inversely related, with the strongest associations in medically naïve samples, which is noteworthy because such samples should involve fewer confounds. One clinical implication is that the lipids of patients treated for depression should be monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
96
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 55 publications
14
96
4
1
Order By: Relevance
“…Finally, they were more likely to be a current smoker and to drink more units of alcohol per week; had lower total cholesterol, and were more likely to have a physical illness. A recent meta-analysis also found that low cholesterol levels have been observed in those with depression, perhaps as a result of candidate mechanisms such as suppressed appetite, cytokine activation, and reduced availability of serotonin (39). The same differences emerged for those with and without GAD except there were no differences in total cholesterol.…”
Section: Major Depressive Disorder and Generalised Anxiety Disordermentioning
confidence: 85%
“…Finally, they were more likely to be a current smoker and to drink more units of alcohol per week; had lower total cholesterol, and were more likely to have a physical illness. A recent meta-analysis also found that low cholesterol levels have been observed in those with depression, perhaps as a result of candidate mechanisms such as suppressed appetite, cytokine activation, and reduced availability of serotonin (39). The same differences emerged for those with and without GAD except there were no differences in total cholesterol.…”
Section: Major Depressive Disorder and Generalised Anxiety Disordermentioning
confidence: 85%
“…Dimopoulos found a correlation between low TC and depression in the elderly patients [73]. Shin in a meta-analysis [74] found that higher TC was associated with lower levels of depression. De Berardis and co. found that TC is low in all clinical groups with bipolar disorder [75].…”
Section: Affective Disordersmentioning
confidence: 99%
“…A recent study [27] found, based on a longitudinal design in which five waves of data were analyzed, that SRH unidirectionally predicted depressive symptoms while the reverse causation hypothesis was not supported. High levels of depressive symptoms were shown in a meta-analytic study [38] to be related to high levels of HDL-C and to low levels of LDL-C (the latter meta-correlation was not significant, however).…”
Section: Introductionmentioning
confidence: 86%